2019
DOI: 10.1182/blood-2019-127029
|View full text |Cite
|
Sign up to set email alerts
|

Bosutinib in the Real-Life Treatment of Chronic Phase Chronic Myeloid Leukemia (CML) Patients Aged > 65 Years Resistant/Intolerant to Frontline Tyrosine-Kynase Inhibitors

Abstract: Background Bosutinib is a 2nd generation tyrosine-kinase inhibitor (TKI) active in Chronic Myeloid Leukemia (CML) patients resistant or intolerant to frontline imatinib, dasatinib or nilotinib; the favourable toxicity profile makes bosutinib potentially useful in elderly patients, but at present there are no data in unselected cohorts of these subjects. Aim To highlight this issue, a real-life cohort of 91 patients followed in 21 Italian Centers and treated with bosutinib when aged > 65 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The analysis of the patients' characteristics showed that the comorbidity profile was in line with the age trend and that bosutinib tends to be prescribed to older patients in both 2nd L and ≥3rd L cohorts. In this direction, RCTs are currently ongoing [13] on the use of bosutinib in older population, and real-life studies evaluated the efficacy of this drug on elderly patients with intolerance/resistance to other TKIs [14], suggesting an increased use of bosutinib in this sub-population. This tendency could also explain the switch to bosutinib as 3rd L observed in the analysis of line sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the patients' characteristics showed that the comorbidity profile was in line with the age trend and that bosutinib tends to be prescribed to older patients in both 2nd L and ≥3rd L cohorts. In this direction, RCTs are currently ongoing [13] on the use of bosutinib in older population, and real-life studies evaluated the efficacy of this drug on elderly patients with intolerance/resistance to other TKIs [14], suggesting an increased use of bosutinib in this sub-population. This tendency could also explain the switch to bosutinib as 3rd L observed in the analysis of line sequence.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective real-world study of bosutinib use in 91 elderly (>65 years) patients with CP-CML, all grade hematological and extrahematological toxicities were reported in 13.1 and 49.4% patients, respectively, after 18.1 months median period of treatment. 46 Among the 86 elderly patients evaluable for response, approximately 4.6% achieved hematological response and 82.5% achieved CCyR (MCyR: 4.7%, CCyR: 77.9%). 46 Furthermore, bosutinib may be better tolerated at lower doses (300 mg QD) in elderly patients.…”
Section: Bosutinib In Elderly and Vulnerable Populationmentioning
confidence: 93%
“…Sixty seven percent of patients achieved MMR or deeper with a discontinuation rate of 26.4%. Therefore, lower dose of bosutinib can be considered in frail patients with severe comorbidities who failed multiple TKI therapies ( 77 ).…”
Section: Dose Modification Of Tkismentioning
confidence: 99%